1995
DOI: 10.2494/photopolymer.8.241
|View full text |Cite
|
Sign up to set email alerts
|

Nematic homogeneous photo alignment by polyimide exposure to linearly polarized uv.

Abstract: Exposure of positive-type polyimide (PI) to linearly polarized deep UV (DUV) light (257nm) induced homogeneous alignment of nematic liquid crystals. The alignment state changed markedly at a particular energy of the UV light. Measurement of the UV absorption spectrum and retardation change generated in PI films by UV irradiation showed that anisotropic alignment was caused by a new mechanism, photodepolymerization of polyimide main chains parallel to the electric field of the DUV light.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
120
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 193 publications
(122 citation statements)
references
References 4 publications
1
120
1
Order By: Relevance
“…To elucidate a basic concept of photodegradation effect, we would like to revisit original works of literature. Hasegawa and Taira [30] first reported that a PI film exposed to linearly polarized ultraviolet (LPUV) light induces a uniform parallel (homogeneous) alignment of LC molecules. The average molecular orientation of the LC molecules is parallel to the film surface and perpendicular to the polarization direction of the LPUV light.…”
Section: Introductionmentioning
confidence: 99%
“…To elucidate a basic concept of photodegradation effect, we would like to revisit original works of literature. Hasegawa and Taira [30] first reported that a PI film exposed to linearly polarized ultraviolet (LPUV) light induces a uniform parallel (homogeneous) alignment of LC molecules. The average molecular orientation of the LC molecules is parallel to the film surface and perpendicular to the polarization direction of the LPUV light.…”
Section: Introductionmentioning
confidence: 99%
“…an isomerization type 2)3) , a dimerization type 4) and a degradation type 5) , according to alignment-ability generation mechanism. Since it is frequently observed that the degradation type of PAF generates unnecessary over decomposed product during UV irradiation process 9) , the isomerization type of PAF is more preferable to simplify the manufacturing process of LCD, which can omit degradation materials removal steps, and we have put isomerization type PAF into practical production for fringe field switching (FFS) LCDs.…”
Section: Introductionmentioning
confidence: 99%
“…Photochemical processes control LC orientation through a photochemical reaction, for example, photoisomerization, photocrosslinking or photodegradation. [8][9][10][11][12][13][14] In contrast, a photophysical process exploits the nonlinear optical (NLO) effects of an LC. 7,15 When a homeotropic LC is vertically irradiated with linearly polarized light, the interaction between the optical field and the LC molecules generates a torque to rotate the molecular director along the polarization direction, leading to homogeneous (in-plane) orientation.…”
Section: Introductionmentioning
confidence: 99%